Answer:
The product of the other two zeros is c
Step-by-step explanation:
Let α, β and γ be the zeros of the polynomial x³ + ax² + bx + c. Since one of the zeros is -1, therefore let γ = -1. Hence:
sum of the roots = α + β + γ = -a
-1 + β + γ = -a
β + γ = -a + 1
αβ + αγ + βγ = b
-1(β) + (-1)γ + βγ = b
-β -γ + βγ = b
Also, the product of the zeros is equal to -c, hence:
αβγ = -c
-1(βγ) = -c
βγ = c
Hence the product of the other two zeros is c
Answer:
The value that represents the 90th percentile of scores is 678.
Step-by-step explanation:
Problems of normally distributed samples are solved using the z-score formula.
In a set with mean
and standard deviation
, the zscore of a measure X is given by:
![Z = \frac{X - \mu}{\sigma}](https://tex.z-dn.net/?f=Z%20%3D%20%5Cfrac%7BX%20-%20%5Cmu%7D%7B%5Csigma%7D)
The Z-score measures how many standard deviations the measure is from the mean. After finding the Z-score, we look at the z-score table and find the p-value associated with this z-score. This p-value is the probability that the value of the measure is smaller than X, that is, the percentile of X. Subtracting 1 by the pvalue, we get the probability that the value of the measure is greater than X.
In this problem, we have that:
![\mu = 550, \sigma = 100](https://tex.z-dn.net/?f=%5Cmu%20%3D%20550%2C%20%5Csigma%20%3D%20100)
Find the value that represents the 90th percentile of scores.
This is the value of X when Z has a pvalue of 0.9. So X when Z = 1.28.
![Z = \frac{X - \mu}{\sigma}](https://tex.z-dn.net/?f=Z%20%3D%20%5Cfrac%7BX%20-%20%5Cmu%7D%7B%5Csigma%7D)
![1.28 = \frac{X - 550}{100}](https://tex.z-dn.net/?f=1.28%20%3D%20%5Cfrac%7BX%20-%20550%7D%7B100%7D)
![X - 550 = 100*1.28](https://tex.z-dn.net/?f=X%20-%20550%20%3D%20100%2A1.28)
![X = 678](https://tex.z-dn.net/?f=X%20%3D%20678)
The value that represents the 90th percentile of scores is 678.
Answer:
Which question needs to be answered?
9514 1404 393
Answer:
(-8)(1) = -8
Step-by-step explanation:
The multiplicative identity element is 1. Multiplying by 1 does not change the value. This is illustrated by ...
(-8)(1) = -8